Define F n ( x ) = k = 1 ∏ n ( sin 2 k x + cos 2 k x )
If F 2 0 1 5 ( 6 π ) = c 2 b − 1 a 2 b − 1 − 1
Then find the value of a + b + c .
Clarification
The power of a in numerator is 2 b − 1 whereas the power of c in denominator is 2 b − 1
a , b , c are positive integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Kartik Sharma @Oussama Boussif Thanks ⌣ ¨
Did the exact same! Nice problem!
Just BRILLIANT
Easy question Kishlaya . Btw how did you fare in today's exam ?
Log in to reply
Actually, I am from ISC Board, so I guess that question doesn't applies to me.
Log in to reply
Oh , ok . I didn't know that .
Brilliant has enabled me to know people from all the diff. Boards , cool !!
So when are your exams ?
Right off the bat, we know that sin x = 2 1 and cos x = 2 3 so we can simplify the product to F 2 0 1 5 ( x ) = k = 1 ∏ 2 0 1 5 ( ( 2 1 ) 2 k + ( 2 3 2 1 ) 2 k ) = k = 1 ∏ 2 0 1 5 ( 2 2 k 1 + 3 2 k − 1 ) = ∏ k = 1 2 0 1 5 ( 2 2 k ) ∏ k = 1 2 0 1 5 ( 1 + 3 2 k − 1 )
We continue by evaluating the top and the bottom individually. For the denominator, we have k = 1 ∏ 2 0 1 5 ( 2 2 k ) = 2 ∑ k = 1 2 0 1 5 2 k = 2 2 2 0 1 6 − 2
And for the numerator, we have k = 1 ∏ 2 0 1 5 ( 1 + 3 2 k − 1 ) = 2 3 2 2 0 1 5 − 1 which follows from the fact that k = 1 ∏ q ( 1 + a 2 k − 1 ) = a − 1 a 2 q − 1 which can be proven easily by induction. Putting these results together, we get ∏ k = 1 2 0 1 5 ( 2 2 k ) ∏ k = 1 2 0 1 5 ( 1 + 3 2 k − 1 ) = 2 2 2 0 1 6 − 2 2 3 2 2 0 1 5 − 1 = 2 2 2 0 1 6 − 1 3 2 2 0 1 5 − 1 .
Now for the hard part: our final answer is 3 + 2 0 1 6 + 2 = 2 0 2 1 .
Problem Loading...
Note Loading...
Set Loading...
First, we try to simplify the given expression. (Although, you can substitute back the values of sin 6 π and cos 6 π to make your work easier) but I'll present a general solution.
Multiplying the expression by cos 2 x − sin 2 x , to simplify it as follows :
F n ( x ) ( cos 2 x − sin 2 x ) F n ( x ) cos 2 x = = = = = ( cos 2 x − sin 2 x ) k = 1 ∏ n ( cos 2 n x + sin 2 n x ) ( cos 2 x − sin 2 x ) ( cos 2 x + sin 2 x ) ( cos 4 x + sin 4 x ) … ( cos 2 n x + sin 2 n x ) ( cos 4 x − sin 4 x ) ( cos 4 x + sin 4 x ) … ( cos 2 n x + sin 2 n x ) ( cos 8 x − sin 8 x ) ( cos 8 x + sin 8 x ) … ( cos 2 n x + sin 2 n x ) . . . ( cos 2 n + 1 x − sin 2 n + 1 x )
Thus, F n ( x ) = cos 2 x cos 2 n + 1 x − sin 2 n + 1 x
We need to compute F 2 0 1 5 ( 6 π )
F 2 0 1 5 ( 6 π ) = = = = cos ( 3 π ) cos 2 2 0 1 6 ( 6 π ) − sin 2 2 0 1 6 ( 6 π ) ( 2 3 ) 2 2 0 1 6 − ( 2 1 ) 2 2 0 1 6 × 2 1 1 2 2 2 0 1 6 − 1 3 2 2 0 1 6 − 1 2 2 2 0 1 6 − 1 3 2 2 0 1 6 − 1 − 1
And thus, a = 3 , b = 2 0 1 6 , c = 2 ⇒ a + b + c = 2 0 2 1